August Heckscher papers - Heckscher, August, 1913-1997.
Correspondence, speeches, writings, and other papers relating to Heckscher's work as an arts consultant in the White House during John F. Kennedy's administration, editorial writer at the New York Herald Tribune, director of the Twentieth Century Fund, and parks commissioner and administrator of recreation and cultural affairs for the Parks, Recreation and Cultural Affairs Administration, New York, N.Y. Subjects include New York, N.Y., urban life, city planning, public architecture, parks, leisure in modern life, and Woodrow Wilson. Organizations represented include the American Council for Nationalities Service, Council on Foreign Relations, Fred L. Lavanburg Foundation, International House, New York, N.Y., John F. Kennedy Center for the Performing Arts, the international council of the Museum of Modern Art, New York, N.Y., the Rockefeller Brothers Fund, the Woodrow Wilson Foundation, and Yale University.
Author, arts consultant, social commentator, and journalist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Kennedy, John F. -- 1917-1963.; Wilson, Woodrow, -- 1856-1924.; New York (N.Y.). -- Parks, Recreation and Cultural Affairs Administration; United States. -- White House Office; American Council for Nationalities Service; Council on Foreign Relations; Fred L. Lavanburg Foundation; International House (New York, N.Y.); John F. Kennedy Center for the Performing Arts (U.S.); Museum of Modern Art (New York, N.Y.); Rockefeller Brothers Fund; Twentieth Century Fund; Woodrow Wilson Foundation; Yale University; New York herald tribune; City and town life; City planning; Leisure; Parks; Parks -- New York (State) -- New York; Public architecture; New York (N.Y.); Authors; Commentators; Consultants; Journalists